Literary illumination : the evolution of artificial light in nineteenth-century literature - Leahy, Richard (Cardiff : University of Wales Press, 2018)
An investigation into the connections between illumination and literature; exploring the spaces between light and dark symbolism through an analysis of artificial light.
The Lightscape of the Early Twentieth Century: Why Stop Here?The Key Ideas: Blurring of Archetypes, Modernity and the Individual; Notes; Bibliography; Index; Back Cover
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed September 28, 2018).
JSTOR
Keywords: Literature, Modern -- 19th century -- History and criticism; Light and darkness in literature; Littérature -- 19e siècle -- Histoire et critique; Lumière et ténèbres dans la littérature.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Light and darkness in literature; Literature, Modern; Beleuchtung; Dunkelheit; Helligkeit; Literatur; HISTORY / Modern / 19th Century; 1800-1899; Criticism, interpretation, etc